DYSFUNCTIONS AND HIDDEN COSTS AT THE UNIVERSITY OF SOCIAL SCIENCES AND MANAGEMENT OF BAMAKO : A QUALIMETRIC DIAGNOSIS AND A SKETCH OF QUANTIFICATION - GOITA, Mamadou Lamine; THERA, Soboua (Revue Internationale du Chercheur, 2025)
Abstract The University of Social Sciences and Management of Bamako (USSGB), like many professional bureaucracies, faces structural and organizational difficulties that hinder its performance. The study, based on the hidden costs method of Savall and Zardet, highlights recurrent dysfunctions: mismatch between staffing needs and assignments, chaotic movements, demotivation, absenteeism, indiscipline, violence on campus, underfunding for training programs, lack of financial partners, and outdated infrastructure. The main causes identified stem from a governance deficit (lack of clear standards, poor communication), a chronic lack of financial and material resources, as well as an internal climate weakened by social and political tensions.